piRNAs in neurodegenerative diseases: Mechanisms of pathogenesis and therapeutic potential - Jheremy Sebastian Reyes Barreto; Juan Sebastian Aguirre Patiño; Laura Tatiana Picón Moncada; Raul Fernando Vega Alvear (Acta Neurológica Colombiana)
Introduction: Neurodegenerative disorders (NDs), such as Alzheimer's disease (AD), Parkinson's disease (PD), and amyotrophic lateral sclerosis (ALS), and tauopathies are highly prevalent and cause significant public health concerns globally. Although research has focused on pathological proteins such as ?-amyloid, the growing interest in non-coding RNAs, including piRNAs, is shifting the understanding of neurodegenerative disorder mechanisms.